Analisis Faktor Determinan Tingkat Partisipasi Pemilih Penyandang Disabilitas Pada Pemilihan Umum 2019 - Liza Noviani; Subhilhar Subhilhar; Muryanto Amin (PERSPEKTIF, 2021)
The manifestation of democratic values in Indonesia as the actualization of power in the hands of the people is the implementation of general elections (Pemilu) and regional head elections. 2019 was a democratic party for the people of Banda Aceh City because it held regional head elections (pilkada) and 2019 simultaneous elections. The lack of impartiality for people with disabilities, including the management of election accessibility for persons with disabilities in previous elections and local elections, made researchers interested in conducting election accessibility research. for persons with disabilities in Banda Aceh City for holding regional head elections (Pilkada) and simultaneous elections 2019. This research uses descriptive qualitative research methods. This research requires data to conclude the research results, there are two types of data used in this study, namely primary data and secondary data. To explore data and information, researchers will conduct interviews with key informants and key informants, non-participant observation and through literature study by studying literature sourced from books, electronic journals, newspapers, regulations and documents related to research topics.